g-CLOSED SETS IN BITOPOLOGICAL SPACES - Hamant Kumar; M. C. Sharma (EPRA International Journal of Research and Development (IJRD), 2022)
In this paper, a new class of sets namely pgη-closed, pgη-closure of a set and pgη-neighbourhood in bitopological spaces are introduced and some of their basic properties are discussed. The relationships among closed, a-closed, s-closed, η-closed, gη-closed and other generalized closed sets are investigated. Several examples are provided to illustrate the behavior of these new class of sets.